Sensory Evaluation and Acceptability of Hand Sanitizer produced from Local Raw Materials –Garlic (Allium Sativum), Aloe Vera (Aloe Barbadensis Miller) and Ethyl Alcohol - J .A, Ezeoguine; P.N., Ezema; U.E, Nnubia (Journal of Home Economics Research, 2024)
This study focused on sensory evaluation and general acceptability of hand sanitizer (verabeny) produced from local raw materials – garlic and aloe vera with 30% ethyl alcohol. Verabeny hand sanitizer was produced and compared with two other types of commercial alcohol – based (60% - 70%) hand sanitizer’s purchase from local market. Sensory attributes studies included: colour, texture, and odour. General acceptability was also compared. A 5-point hedonic rating scale was used for data collection. The panel of judges was drawn from a group of Home Economics students. Data were analyzed using means. The result indicated that verabeny compared well with the two commercial hand sanitizer samples in all sensory attributes except odour.